Perancangan Sistem Informasi Inventory Barang Elektronik Berbasis Website Pada CV Jabbar Global Sinergi - Elgiawan Sulistio; Risah Subariah; Eko Surhayanto; Afrizal Zein (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Jabbar Global Sinergi is an online store engaged in the electronics sector, located in the South Tangerang area. This shop sells various kinds of electronic components and accessories and several other spare parts, in its operations Jabbar Global Synergy still uses the manual method, which is recorded in a book to record goods so that errors often occur in the stock data, and the lack of time efficiency in searching for goods makes it difficult to obtain data online.realtime.This study aims to design information systemsinventory website-based electronic goods on cv jabbar global synergy to facilitate data collection while increasing time efficiency making it easier to obtain data or information onlinerealtime. The expected result of this research is to be able to build and design information systemsinventory website-based electronic goods to make it easier to get information about data and goods reports onlinerealtime.